International Relation on Peace and in Islam: Implementation of Diplomacy in Ottoman Era - Mhadsri, Saranyu; Suetair, Abdulroning; Ardam, Sarfee (MENARA : Journal of Islamic and Contemporary Issues, 2024)
This research aimed to 1) Study the International Relation on Peace and War in Islam 2) Study Diplomatic Practices in the Ottoman Era 3) Study Diplomacy protocol in the Ottoman Era 4) Present salient features of Implementation in the Ottoman Era which can be adapted in contemporary world by using qualitative methodology historical approach study on academics books, article, media etc. in primary, secondary and tertiary sources searching transformation and development of Ottoman Diplomacy in three period 1) Rise Era (1299-1453) 2) Middle Era ( 1453-1566) and Fallen Era (ค.ศ.1566-1923) presented the result in analytical description methodology. The result show that 1) International Relation on Peace and War in Islam relied on Al-Quran, Sunnah and Practices of the Holy Companion 2) The Implementation of Diplomacy in Early Ottoman Era using Hanafites’s Ilm-Siyar with Ottoman’s traditional law up to 18th Century 3) The Ottoman Empire emphasized on Diplomatic Practices systematically and respected on their guest 4) The Ottomans have salient features were Respect, Innovate and Compromise. The research suggested that the Muslim leaders and Diplomats should implemented the result in sake of peacebuilding between Muslim and Non-Muslim Community.